Frequent torsades de pointes in a child with novel AKAP9 mutation: A case report and literature review - Wang, Yefeng; Zuo, Chao; Wang, Xiang; Xiao, Yunbin; Liu, Qiming; Chen, Zhi (Frontiers in Pediatrics, 2023)
Introduction The aim of the present study was to report the diagnosis and treatment of a rare case of frequent torsades de pointes (Tdp) in a child with a novel AKAP9 mutation. A 13-year-old girl suffered from repeated syncope and frequent Tdp. An electrocardiogram (ECG) showed frequent multisource premature ventricular contractions with R-ON-T phenomenon. The QTc ranged from 410 ms to 468 ms. The genetic test indicated a heterozygous mutation, namely, c.11714T>C (p.M3905T), in the AKAP9 gene, which is a controversial gene in long QT syndrome. After treatment with propranolol, recurrent syncope occurred, and the patient received an implantable cardioverter defibrillator (ICD). Due to frequent electrical storms at home, the child was additionally treated with propafenone to prevent arrhythmia. The antitachycardia pacing (ATP) function in the ICD was turned off, and the threshold of ventricular tachycardia (VT) assessment was adjusted from 180 beats/min to 200 beats/min. The patient was followed up for 12 months without malignant arrhythmia and electric shock. Conclusion Genetic testing may be a useful tool to determine the origin of channelopathy, but the results should be interpreted in combination with the actual situation. Rational parameter settings for the ICD and application of antiarrhythmic drugs can reduce the mortality of children.